Studi Bioakumulasi Logam Berat Merkuri (Hg) pada Teripang Lokal (Phyllophorus sp.) dari Pantai Timur Surabaya – Jawa Timur [Study Of Bioaccumulation Heavy Metal Mercury (Hg) On Local Sea Cucumber (Phyllophorus sp.) from Surabaya East Coast – East Java] - Endang Dewi Masithah; Rr. Febrina Anggraini Putri; Muhammad Arief (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Sea cucumber is a commodity fishery that is traded international. One of the sea cucumber that has economic value is the local sea cucumber (Phyllophorus sp.) believed that contain compounds can be immunomodulatory. Phyllophorus sp. is one of the three dominant species of sea cucumbers in abundance and distribution in the Surabaya East Coast (Winarni,dkk., 2010). Coastal environmental issues that deserve the attention is the problem of heavy metal pollution in coastal waters. The highest toxicity of heavy metals for aquatic animals and humans are mercury (Hg) (Widowati dkk, 2008). The purpose of this study was to determine levels of heavy metals bioaccumulation of mercury (Hg) in the local sea cucumber (Phyllophorus sp.) From the East Coast Surabaya and to determine the heavy metal content of mercury (Hg) in the local sea cucumber (Phyllophorus sp.) has exceeded the threshold or does not. The experiment was conducted on the East Coast Surabaya and analisys of heavy metal Mercury (Hg) in Balai Besar Laboratorium Kesehatan (BBLK) Surabaya. The method used is the method of field observation and analyzed descriptively. The results showed levels of mercury bioaccumulation of heavy metals (Hg) from BCFo-w value from 454.78– 802.05 and BCFo-s from 31,42 – 111,26. This shows Phyllophorus sp. have the ability to accumulate heavy metals with low until middle accumulation level category. Mercury content of the Phyllophorus sp. obtained range from 0.031 to 0.061 ppm, sea water ranged from 0.0015 to 0.0023 ppm and sediments ranged from 0.0417 to 0.112 ppm. Mercury levels in Phyllophorus sp. and sediment is below the NAB, but the sea water has exceeded from NAB. Water quality parameters are still in normal conditions in accordance with the quality standards KMLH (2004) that temperatures 26-28 º C, pH 7-8, salinity ranged from 28-29